Optimalisasi Tugas dan Fungsi DPRD dalam Mewujudkan Pemerintahan Bersih - Santoso, Rudi; Shulton A, Habib; Mu'in, Fathul; Fikri, Arif (Universitas Islam Negeri Raden Intan Lampung, 2021)
DPRD has a strategic position in the development of an area. Because, the people's representative institution has three inherent functions, namely the function of making local regulations (legislation), supervision (controlling) and budget function (bugeting). However, the reality of the implementation of the dprd function is still not optimal. This is due to the incomprehension of legislators in describing legislation, even more extreme, the existence of the function is not to assist local governments in carrying out government duties but rather as a tool for personal and party interests. This writing uses normative juridical research methods, where the author uses laws, journal articles, books and documents that support in discussing the issue of optimizing the tasks and functions of dprd members in realizing clean government. This study concluded, good governance can be done by optimizing and improving the quality of dprd members by improving the quality and understanding of DPRD members to their duties and functions. The fruit of quality improvement can be measured by how much the role of the DPRD in terms of partnership with executive institutions in making local regulations, drafting budgets, and in monitoring the course of government.